Is NSGA-II Ready for Large-ScaleMulti-Objective Optimization? - Nebro-Urbaneja, Antonio Jesús; Galeano-Brajones, Jesús; Luna-Valero, Francisco; Coello Coello, Carlos A. (MDPI, 2022)
NSGA-II is, by far, the most popular metaheuristic that has been adopted for solving multi-objective optimization problems. However, its most common usage, particularly when dealing with continuous problems, is circumscribed to a standard algorithmic configuration similar to the one described in its seminal paper. In this work, our aim is to show that the performance of NSGA-II, when properly configured, can be significantly improved in the context of large-scale optimization. It leverages a combination of tools for automated algorithmic tuning called irace, and a highly configurable version of NSGA-II available in the jMetal framework. Two scenarios are devised: first, by solving the Zitzler–Deb–Thiele (ZDT) test problems, and second, when dealing with a binary realworld problem of the telecommunications domain. Our experiments reveal that an auto-configured version of NSGA-II can properly address test problems ZDT1 and ZDT2 with up to 217 = 131, 072 decision variables. The same methodology, when applied to the telecommunications problem, shows that significant improvements can be obtained with respect to the original NSGA-II algorithm when solving problems with thousands of bits.
Keywords: Programación heurística; Algoritmos genéticos; Computación evolutiva; Optimización matemática; NSGA-II; Auto-configuration and auto-design of metaheuristics; Large-scale multi-objective optimization; Real-world problems optimization